RELATIONSHIP OF ADHERENCE, SELF EFFICACY, SOCIAL SUPPORT, QUALITY OF HEALTH CARE, AND PSYCHOLOGICAL RESPONSE OF PARENS TOWARDS QUALITY OF LIFE OF CHILDREN WITH TUBERCULOSIS IN YOGYAKARTA, INDONESIA - Lely Lusmilasari; Akhmadi Akhmadi; Rochma Dwi Rahayu; Jeki Rahmawati; Ardhy Khartika; Sefti Rukmana (Belitung Raya Foundation, Indonesia, 2017)
Background: Quality of life includes the aspects of physical, emotional, social function, welfare and perceptions about life. Quality of life of children with tuberculosis is considered lower than the quality of life of healthy children. Little is known about the factors related to the quality of life of children with tuberculosis, especially in Yogyakarta, Indonesia. Objective: This study aims to examine the relationships of adherence, social support, quality of healthcare, self-efficacy, and psychological response of parents towards quality of life of children with tuberculosis in Yogyakarta, Indonesia. Methods: This study employed a cross-sectional correlation design, which was conducted from April to November 2016, and involved 41 caregivers and children with tuberculosis according to research criteria. A consecutive sampling was applied to determine sample size. Data were analyzed by bivariate and multivariate analysis using SPSS with significant level p=0.05 and confidence interval = 95%. Results: Findings showed significant relationships between social support, psychosocial response, mainly anxiety and stress (p<0.05) with quality of life. While adherence, self-efficacy, and quality of healthcare did not have significant relationship (p>0.05) with quality of life. The results of multivariate analysis showed significant relationships between social support with r =0.305 (CI95%:0.134-0.188; p=0.026), psychosocial response of caregiver, mainly level of stress with r= 0.425 (CI95%:-1.369-0.126; p=0.007) and anxiety with r= 0.378 (CI95%: -0.107-1.692; p=0.03) and quality of children life (R square=0.278). The strongest variable related to quality of children life was psychosocial response (anxiety) of parents (r=0.425). Conclusions: Quality of life in children with tuberculosis is related to social support and psychosocial response of parents. The dominant factor is psychosocial responses of anxiety.